(untitled) (Indian Journal of Chemistry (IJC), 2023)
Density functional theory studies were performed on a series of highly substituted imidazole and indole derivatives. Heats of formation were calculated using B3LYP functional with 6-31G basis sets by designing isodesmic reaction conditions. General trend observed in the case of highly substituted imidazoles is that as substitution increases the heat of formation increases. The HOF of 1,2,4,5-tetraphenyl 1-H imidazole is the largest (131.28 kJ/mol) and the HOF of 2-(4-chlorophenyl)- 1- benzyl-4,5- diphenyl -1H imidazole (H) is the smallest (85.82 kJ/mol) at the B3LYP/6-31G level. The relative stability of the substituted imidazoles was evaluated based on the calculated HOFs and the energy gap between the frontier molecular orbitals.